2011
DOI: 10.1002/pd.2624
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal screening for Down syndrome: a survey of willingness in women and family physicians to engage in shared decision‐making

Abstract: Overall, the women and their FPs wished to engage in SDM as regards prenatal Down-syndrome screening. Only a few factors influenced this desire which therefore may be modifiable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 27 publications
3
44
0
1
Order By: Relevance
“…These findings are congruent with earlier research on SDM implementation in this context [26], which showed that attitude, subjective norm, self-efficacy, and moral norm were determinants of pregnant women’s intention to engage in SDM. Although the variables “descriptive norm” and “anticipated regret” were not investigated in the earlier study, the influence of social pressure came out through the subjective norm variable, which refers to the influence of significant individuals in women’s entourage.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are congruent with earlier research on SDM implementation in this context [26], which showed that attitude, subjective norm, self-efficacy, and moral norm were determinants of pregnant women’s intention to engage in SDM. Although the variables “descriptive norm” and “anticipated regret” were not investigated in the earlier study, the influence of social pressure came out through the subjective norm variable, which refers to the influence of significant individuals in women’s entourage.…”
Section: Discussionsupporting
confidence: 91%
“…Our results support earlier research on SDM implementation indicating that women showed a strong intention to engage in SDM regarding prenatal screening for Down syndrome [26]. Moreover, this high level of intention may reflect a need felt by pregnant women facing prenatal screening choices to become more skilled in discussing screening tests with their health care provider, which is congruent with the literature on pregnant women’s decision-making needs [4,6,9].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…First, there was a ceiling effect, with physicians showing high scores on all these measures before the intervention. Since patient and public involvement is getting popular and physicians are more aware of SDM, it is not surprising that we observed high intention, as other studies have done [17,34]. Second, the TPB defines and distinguishes between several precise behaviors in great detail [35].…”
Section: Discussionmentioning
confidence: 54%
“…In addition, not all clinicians are convinced of the benefits of SDM (33)(34)(35). Patient-reported barriers for SDM are their lack of awareness about having a choice, low confidence in their capacity to participate, a self-perceived lack of knowledge, low health literacy, low numeracy skills and uncertainty about what questions to ask (36)(37)(38)(39)(40)(41).…”
Section: Barriers To Shared Decision-makingmentioning
confidence: 99%